Step by step optimization of a sperm cryopreservation protocol for spotted wolffish (Anarhichas minor Olafsen, 1772) - Santana, J. (2020)
Spotted wolffish Anarhichas minor reproduction in captivity is dependent on in vitro fertilization. However, low sperm volume with relatively low cell concentration and the lack of gametes synchronization (simultaneous availability of mature eggs and sperm) represent a challenge for the industry. Thus, the development of protocols for sperm storage are crucial. Four sequential experiments were conducted to optimize a sperm cryopreservation protocol for this species. First, three different cryoprotectants (DMSO; 1, 2-propanediol; and methanol) at different concentrations (5, 10, and 20%) were tested for their toxicity. No significant differences (p > 0.05) were detected between the control samples and cryoprotectants at concentration up to 10% DMSO, 10% propanediol, and 20% methanol in terms of motility parameters. Second, using the highest non-toxic concentrations of cryoprotectants, sperm was cryopreserved in 0.5 mL straws, at different distances from the liquid nitrogen (1.5, 2.5, 4.5, and 7.5 cm) that correspond to different freezing rates. Motility parameters after freezing/thawing decreased for all the cryoprotectants (p < 0.001), however, methanol had the lowest protective capacity while DMSO the highest. Afterwards, two different thawing rates (1 min at 5 °C; and 25 s at 10 °C) were tested using only 10% DMSO and 10% propanediol. Both for the DMSO and propanediol, there were no significant differences (p > 0.05) between the two thawing rates. The best results were obtained using 10% DMSO. Finally, the fertilization capacity of cryopreserved sperm (10% DMSO and thawed at 5 °C for 1 min) was tested against fresh sperm using two spermatozoa:egg ratios and 4 h gametes contact time. The ratio of eggs with normal cell cleavage, abnormal cleavage or undeveloped were counted at the 2-4 cell stage. Cryopreserved sperm showed lower fertilization capacity at a concentration of 5 × 104 spermatozoa:egg compared with fresh sperm (p < 0.001). At a concentration of 5 × 105 spermatozoa:egg, similar fertilizations rates to the fresh sperm were obtained. The presence of the cryoprotectant DMSO during the 4 h contact time did not affect the fertilization rate or the percentage of embryos with abnormal cleavage (p > 0.05). To cryopreserve spotted wolffish sperm it is recommended to use 10% DMSO, loaded in 0.5 mL straws, freeze at a height between 4.5 (-14.05 °C/min) and 7.5 cm (-5.9 °C/min) from liquid nitrogen for 10 min and thaw for 1 min at 5 °C (177.9 °C/min). In vitro fertilization with cryopreserved sperm should be performed with a concentration of at least 5 × 105 spermatozoa per egg.